60.2k views
2 votes
Solve using any appropriate method. If the system has an infinite number of solutions, use set-builder notation to write

the solution set. If the system has no solution, state this
13) 4x + 8y = 8
5x + 7y = 1
A) (-8,6)
B) (4,3)
C) (-4,3)
D) No solution
14) 7x + 7y = 8
5x + 5y = 10
A) (10,5)
D) (1,1)
C) {(x,y)|7x + 7y = 8)
B) No solution
15) y = 3x + 4
5x + y = -92
A) No solution
C) (4,8)
B) ((x, y) 5x + y = -92)
D) (-4,-8)
16) 0.4x + 0.4y = 4
0.4x - 0.4y = 1
D)
B)
(659
0(*)
C) (1.4)
D) {x,y) x = 7+ 4y}
17) x - 4y = 1
x= 7+ 4y
A) No solution
B) {(x,y)|x - 4y = 1)​

User Vanval
by
5.4k points

1 Answer

4 votes

Answer:


13.\ (x,y) = (-4,3)


14.\ No\ Solution


15.\ (x,y) = (-12,-32)


16.\ (x,y) = (3.75,6.25)


17.\ No\ Solution

Step-by-step explanation:

13)


4x + 8y = 8 ---- (1)


5x + 7y = 1 ------ (2)

Multiply equation by 5 and equation 2 by 4


5(4x + 8y = 8)


4(5x + 7y = 1)


5 * 4x + 5 * 8y = 5 * 8\\4*5x + 4*7y = 4 *1


20x + 40y = 40 ------ (3)


20x + 28y = 4 ------ (4)

Subtract equation 3 from 4


(20x + 28y = 4) - (20x + 40y = 40)


20x - 20x+ 28y -40y= 4-40


-12y = -36

Divide both sides by -12


(-12y)/(-12) = (-36)/(-12)


y = 3

Substitute
y = 3 in equation 1


4x + 8y = 8


4x + 8(3) = 8


4x + 24 = 8

Subtract 24 from both sides


4x + 24 - 24 = 8 - 24


4x = -16

Divide both sides by 4


(4x)/(4) = (-16)/(4)


x = -4


Hence\ (x,y) = (-4,3)

----------------------------------------------

14)


7x + 7y = 8 ---- (1)


5x + 5y = 10 ----- (2)

Make x the subject of formula in (2)


5x + 5y = 10


5x + 5y - 5y = 10 - 5y


5x = 10 - 5y


(5x)/(5) = (10 - 5y)/(5)


x = (10)/(5) - (5y)/(5)


x = 2 - y

Substitute
x = 2 - y in (1)


7x + 7y = 8


7(2-y) + 7y = 8

Open bracket


7*2-7*y + 7y = 8


14 -7y + 7y = 8


14 \\eq 8

At this point, we conclude that thee system has no solution.

----------------------------------------------

15)


y = 3x + 4 --- 1


5x + y = -92 ----2

Substitute
y = 3x + 4 in (2)


5x + 3x + 4 = -92


8x + 4 = -92

Subtract 4 from both sides


8x + 4 -4= -92 -4


8x = -96

Divide both sides by 8


(8x)/(8) = (-96)/(8)


x = -12

Substitute
x = -12 in equation 1


y = 3x + 4


y = 3(-12) + 4


y = -36 + 4


y = -32


Hence\ (x,y) = (-12,-32)

----------------------------------------------

16)


0.4x + 0.4y = 4


0.4x - 0.4y = 1

Add both equations


(0.4x + 0.4y = 4) + (0.4x - 0.4y = 1)


0.4x+0.4x + 0.4y-0.4y = 4+1


0.8x = 5

Divide both sides by 0.8


(0.8x)/(0.8) = (5)/(0.8)


x = 6.25

Substitute
x = 6.25 in (1)


0.4(6.25) + 0.4y = 4


2.5 + 0.4y = 4

Subtract 2.5 from both sides


2.5 -2.5 + 0.4y = 4 -2.5


0.4y = 1.5

Divide both sides by 0.4


(0.4y)/(0.4) = (1.5)/(0.4)


y = (1.5)/(0.4)


y = 3.75


Hence,\ (x,y) = (3.75,6.25)

----------------------------------------------

17)


x - 4y = 1


x= 7+ 4y

Substitute
x= 7+ 4y in (1)


7 + 4y - 4y = 1


7 \\eq 1

At this point, we conclude that thee system has no solution.

User Rushikesh
by
5.7k points